2014
DOI: 10.1007/s10610-014-9265-3
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting the Conceptualisation of Victims of Trafficking for Sexual Exploitation: A Case Study of Brazilians in Spain and Portugal

Abstract: Despite the significant emphasis given to the trafficking of Brazilians to the sex industry of the Iberian Peninsula, the concepts of "victim of trafficking for sexual exploitation" used in these three countries vary. This article analyses the positions of Brazil, Spain and Portugal regarding the conceptualisation of "trafficking victim," focusing on their legislation and policies, as well as on relevant narratives which show how these policies are being applied. It showcases how the incompatible definitions b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Jones et al (1984) describe how a label is applied during the process of stigmatization, which leads to “devastating consequences for emotions, thoughts and behavior” (p. 4). Labels or labeling are in this article thus connected during the process of stigmatization and used similarly to Butler (2009) use of “frames,” which are “politically saturated ways to present a person or deed that lead to assumptions being made about them” (De Pérez, 2015, p. 22). Experiences of stigma and labeling are evident in studies among sex workers (Benoit et al, 2018; De Pérez, 2015; Rocha-Jiménez et al, 2018), victims of sexual violence (Schmitt et al, 2020; Verelst et al, 2014), and victims of human trafficking for sexual exploitation (Dahal et al, 2015).…”
Section: Human Trafficking Stigma and Labeling Of Nigerian Victimsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jones et al (1984) describe how a label is applied during the process of stigmatization, which leads to “devastating consequences for emotions, thoughts and behavior” (p. 4). Labels or labeling are in this article thus connected during the process of stigmatization and used similarly to Butler (2009) use of “frames,” which are “politically saturated ways to present a person or deed that lead to assumptions being made about them” (De Pérez, 2015, p. 22). Experiences of stigma and labeling are evident in studies among sex workers (Benoit et al, 2018; De Pérez, 2015; Rocha-Jiménez et al, 2018), victims of sexual violence (Schmitt et al, 2020; Verelst et al, 2014), and victims of human trafficking for sexual exploitation (Dahal et al, 2015).…”
Section: Human Trafficking Stigma and Labeling Of Nigerian Victimsmentioning
confidence: 99%
“…Labels or labeling are in this article thus connected during the process of stigmatization and used similarly to Butler (2009) use of “frames,” which are “politically saturated ways to present a person or deed that lead to assumptions being made about them” (De Pérez, 2015, p. 22). Experiences of stigma and labeling are evident in studies among sex workers (Benoit et al, 2018; De Pérez, 2015; Rocha-Jiménez et al, 2018), victims of sexual violence (Schmitt et al, 2020; Verelst et al, 2014), and victims of human trafficking for sexual exploitation (Dahal et al, 2015). An important aspect of stigma in those groups is that of “sexual stigma,” “the negative regard, inferior status, and relative powerlessness that society collective accords any nonheterosexual behavior, identity, relationship, or community … They are grounded in society’s power relations” (Herek, 2007, pp.…”
Section: Human Trafficking Stigma and Labeling Of Nigerian Victimsmentioning
confidence: 99%
“…The articles' publication dates range from 2015 (e.g., [15]) to 2020 (e.g., [10,15,16]). The year with the most publications was 2019 (n = 4), followed by 2020 (n = 3), 2016 (n = 2), 2018 (n = 1), and 2015 (n = 1).…”
Section: Main Characteristics Of the Studiesmentioning
confidence: 99%
“…Of the ten qualitative studies, three utilized semi-structured interviews [5,10,16], one, a case study [15], the General Health Questionnaire-28 (GHQ) [14]), documentary research [16], semi-structured interviews and a field diary [17], semi-structured interviews and a literature review [12], and semi-structured interviews, observations, and documentary research [4,9].…”
Section: Design and Instrumentsmentioning
confidence: 99%
“…Among the obstacles related to procedures in the police and judicial investigation, a series of aspects identified in different studies (e.g. de Pérez, 2015) are worth highlighting: the lack of consensus on the definition of trafficking that muddles the boundaries with other crimes (migrant smuggling, enforced prostitution, sexual exploitation or inducement or incitement to prostitution); the absence of agreed indicators for identification, since they vary among countries (Piscitelli, 2012; Surtees, 2008) and even among professionals from the same country (Villacampa and Torres, 2017); the lack of training of the professionals involved in the process of identification and protection (Brunovskis and Surtees, 2019); the places where the identifications are conducted – many through raids with the traffickers present – are not perceived as safe or comforting and neither do they instil a sense of security in the victims, who, thus, resist being identified; the lack of manpower and various resources in the crime investigation (Meneses-Falcón et al, 2015); and inadequate police practices in the procedure (Bjelland, 2017). Some studies of judicial cases of sex trafficking have revealed aspects that have led to the low level of convictions of this crime in the EU.…”
Section: Introductionmentioning
confidence: 99%